2014
DOI: 10.5194/acp-14-12915-2014
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species associated with water-soluble PM<sub>2.5</sub> in the southeastern United States: spatiotemporal trends and source apportionment

Abstract: Abstract. We assess the potential of the water-soluble fraction of atmospheric fine aerosols in the southeastern United States to generate reactive oxygen species (ROS) and identify major ROS-associated emission sources. ROS-generation potential of particles was quantified by the dithiothreitol (DTT) assay and involved analysis of fine particulate matter (PM) extracted from high-volume quartz filters (23 h integrated samples) collected at various sites in different environmental settings in the southeast, incl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
176
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(205 citation statements)
references
References 75 publications
25
176
3
1
Order By: Relevance
“…So far, we have not found reported DTT loss rate values for diesel/biodiesel exhausted particles. However, as it can be observed from Table 5, other studies used similar particle 24 and the reported results from Verma et al, 35 and McWhinney et al 50 (also see Figure 3). We can also conclude oxidative potential of particles emitted from the burning of diesel/biodiesel blends is comparable to fossil diesel-emitted particles.…”
Section: Redox Activity Of Enriched Srm1649b Portionscontrasting
confidence: 35%
See 1 more Smart Citation
“…So far, we have not found reported DTT loss rate values for diesel/biodiesel exhausted particles. However, as it can be observed from Table 5, other studies used similar particle 24 and the reported results from Verma et al, 35 and McWhinney et al 50 (also see Figure 3). We can also conclude oxidative potential of particles emitted from the burning of diesel/biodiesel blends is comparable to fossil diesel-emitted particles.…”
Section: Redox Activity Of Enriched Srm1649b Portionscontrasting
confidence: 35%
“…24,25 For instance, some transition metals (such as Fe and Cu) and organic species (e.g. polycyclic aromatic compounds and quinones or quinone-like compounds) as well as humic-like substances (HULIS), black and brown carbon (BC and BrC) within PM are known to increase the production of ROS either in vitro or in vivo, especially if they are present in fine and ultrafine size range, [4][5][6]24,[30][31][32][33][34][35] since they are able to go more profoundly in the respiratory system. Meanwhile, considering diesel/biodiesel blends exhausts are substantially composed by ever small size PM, such as nanoparticles and/or ultrafine particles rich in semi-volatile organic compounds and trace metals, 1,7,16 it is likely ROS may be contributing to the adverse health effects caused by DEP or even BEP.…”
Section: Introductionmentioning
confidence: 99%
“…Higher wintertime DTT activity has been frequently reported [9,24,26,27,36,53], on the contrary, other studies found higher activity in summer as compared to winter [31,44,47].…”
Section: Seasonal and Spatial Variationsmentioning
confidence: 76%
“…DTT activity is impacted by both local emissions associated by individual site characteristics and regional sources [36]. Some field studies carried out at different locations, with different contributing sources, found higher DTT activity at continuous traffic and underground sites [43], and/or near freeways [24].…”
Section: Seasonal and Spatial Variationsmentioning
confidence: 99%
“…Previous studies (Bates et al, 2015;Fang et al, 2016;Verma et al, 2014) also highlighted the importance of this source to explain the OP AA and DTT. We may explain such high intrinsic OP by the presence of metals in this source -notably the copper (Charrier et al, 2015).…”
Section: Intrinsic Opmentioning
confidence: 99%